2011
DOI: 10.1210/jc.2011-1074
|View full text |Cite
|
Sign up to set email alerts
|

Weight Beneficial Treatments for Type 2 Diabetes

Abstract: Weight-beneficial agents should be considered in patients, particularly obese patients, who fail to reach glycemic targets on metformin therapy. We propose the following treatment choices based on potential weight benefit and blood glucose increment: long-acting GLP-1 agonists (liraglutide), DPP-4 inhibitors, bile acid sequestrants, amylin analogs, and basal insulin for patients with elevated fasting plasma glucose; and short-acting (exenatide) or long-acting GLP-1 agonists, amylin analogs, DPP-4 inhibitors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 126 publications
1
57
0
2
Order By: Relevance
“…Diabetes treatment is important and diabetes medication also affects body composition. 32,[41][42][43] For most types of medication, the effect on weight (either weight gain or weight stability) is evident. 43,44 The effects on specific body composition measures such as muscle mass are largely unknown, although one study found that patients treated with insulin sensitizers (metformin and/or thiazolidinediones) show less decline in muscle mass than untreated patients.…”
Section: Effect Of Type 2 Diabetes On Body Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes treatment is important and diabetes medication also affects body composition. 32,[41][42][43] For most types of medication, the effect on weight (either weight gain or weight stability) is evident. 43,44 The effects on specific body composition measures such as muscle mass are largely unknown, although one study found that patients treated with insulin sensitizers (metformin and/or thiazolidinediones) show less decline in muscle mass than untreated patients.…”
Section: Effect Of Type 2 Diabetes On Body Compositionmentioning
confidence: 99%
“…32,[41][42][43] For most types of medication, the effect on weight (either weight gain or weight stability) is evident. 43,44 The effects on specific body composition measures such as muscle mass are largely unknown, although one study found that patients treated with insulin sensitizers (metformin and/or thiazolidinediones) show less decline in muscle mass than untreated patients. 32 Another explanation for the particularly unfavorable changes in body composition in those with undiagnosed diabetes compared with those with diagnosed type 2 diabetes could be the lifestyle recommendations that persons receive from their physician after diagnosis.…”
Section: Effect Of Type 2 Diabetes On Body Compositionmentioning
confidence: 99%
“…The close link between T2DM and excess body weight highlights the need to consider the weight effects of different treatment regimens, besides their effects on glucose homeostasis 9 . A paradigm shift from a glucocentric to a weight-centric management of T2DM may be proposed, emphasising the urgent need for new treatment strategies 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetologists are well aware that metformin therapy tends to promote a modest degree of weight loss, whereas therapy with sulfonylureas or insulin tends to promote weight gain, often exacerbating the underlying problem (Meneghini et al 2011). Of the newer diabetes therapies, GLP-1 agonists also tend to lower body weight; it is not likely to be accidental that they also activate hepatic AMPK (Meneghini et al 2011;Ben-Shlomo et al 2011).…”
Section: Weight Controlmentioning
confidence: 99%
“…Diabetologists are well aware that metformin therapy tends to promote a modest degree of weight loss, whereas therapy with sulfonylureas or insulin tends to promote weight gain, often exacerbating the underlying problem (Meneghini et al 2011). Of the newer diabetes therapies, GLP-1 agonists also tend to lower body weight; it is not likely to be accidental that they also activate hepatic AMPK (Meneghini et al 2011;Ben-Shlomo et al 2011). Metformin also promotes weight loss in the context of polycystic ovary syndrome and has also been employed with some success to prevent weight gain in patients treated with certain antipsychotic agents (Harborne et al 2005;Nieuwenhuis-Ruifrok et al 2009;Praharaj et al 2011).…”
Section: Weight Controlmentioning
confidence: 99%